In Vitro Comparative Accuracy of PSP Digital Radiography and CBCT for Detection of Broken Nickel-Titanium Files in Endodontically Treated Root Canals - Sharifishoshtari, Sanaz; Jafarzadeh, Mansour; Lalegani, Fateme; Hesabi, Nima (Galen Medical Journal, 2024)
Background: This study aimed to compare the accuracy of indirect photostimulable phosphor (PSP) digital radiography and cone-beam computed tomography (CBCT) for detection of broken nickel-titanium (NiTi) files in endodontically treated root canals. Materials and Methods: This in vitro study was conducted on 108 extracted single-rooted mandibular premolars in 4 group (n=27) of positive control (root canal instrumentation and obturation), negative control (root canal instrumentation without obturation) and two experimental groups of file fracture with and without root canal obturation. The teeth underwent PSP digital radiography and CBCT, and the radiographs were evaluated by one oral radiologist and one endodontist twice. Presence/absence of a broken file in the root canals was reported using a 4-point scale. The sensitivity, specificity, and accuracy were calculated and compared for CBCT and PSP digital radiography. Results: The sensitivity, specificity, and accuracy for detection of broken NiTi files in obturated canals were 51.9%, 59.3% and 55.6%, respectively for CBCT and 70.3%, 85%, and 77.8%, respectively for PSP radiography. These values were 81.4%, 59.3%, and 79.6%, respectively for CBCT and 85.1%, 81.4%, and 83.3%, respectively for PSP radiography in unfilled canals. PSP digital radiography was significantly superior to CBCT for detection of broken files in obturated (P=0.01) but not in unfilled (P=0.420) root canals. Conclusion: Considering the lower radiation dose and higher accuracy of PSP digital radiography than CBCT for detection of broken NiTi files in filled canals, and their comparable accuracy in unfilled canals, PSP digital radiography is recommended for this purpose.